2014
DOI: 10.1128/jcm.01693-14
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Detection of Small Ruminant Bovine Spongiform Encephalopathy within Transmissible Spongiform Encephalopathy Mixes by Serial Protein Misfolding Cyclic Amplification

Abstract: bIt is assumed that sheep and goats consumed the same bovine spongiform encephalopathy (BSE)-contaminated meat and bone meal that was fed to cattle and precipitated the BSE epidemic in the United Kingdom that peaked more than 20 years ago. Despite intensive surveillance for cases of BSE within the small ruminant populations of the United Kingdom and European Union, no instances of BSE have been detected in sheep, and in only two instances has BSE been discovered in goats. If BSE is present within the small rum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Furthermore, PMCA can selectively detect C-BSE in mixtures of brain homogenates (BHs) from C-BSE-and scrapie-infected sheep with 100% specificity and 97% sensitivity (25). Still, it remains important to develop highly sensitive methods that can discriminate C-BSE from other prion strains in cattle.…”
mentioning
confidence: 99%
“…Furthermore, PMCA can selectively detect C-BSE in mixtures of brain homogenates (BHs) from C-BSE-and scrapie-infected sheep with 100% specificity and 97% sensitivity (25). Still, it remains important to develop highly sensitive methods that can discriminate C-BSE from other prion strains in cattle.…”
mentioning
confidence: 99%
“…Recently, a serial protein misfolding cyclic amplification assay (sPMCA) has been developed to specifically detect classic BSE even within the presence of scrapie prions. It has been reported that in a blind trial, this sPMCA-based assay specifically amplified BSE PrP Sc within brain mixes with 100% specificity and 97% sensitivity when BSE agent was diluted into scrapie-infected brain homogenates at 1% (vol/vol) [ 47 ]. Compared to mouse bioassay this in vitro technique may offer a quick, reliable and more cost effective method in detecting BSE in the presence of scrapie.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of AHQ/AHQ substrate did not support the amplification of any classical or atypical/Nor98 scrapie isolates from sheep with a range of PRNP genotypes. These observations have been developed into a sensitive assay using a combination of the VRQ/VRQ and AHQ/AHQ brain homogenate substrates [ 113 ]. These two substrates encourage the amplification of BSE over scrapie and when used in sequential rounds of PMCA have demonstrated amplification specificity to BSE, even when BSE is present with a vast excess of different scrapie isolates [ 113 , 114 ].…”
Section: In Vitro Replication Of Prion Typesmentioning
confidence: 99%
“…These observations have been developed into a sensitive assay using a combination of the VRQ/VRQ and AHQ/AHQ brain homogenate substrates [ 113 ]. These two substrates encourage the amplification of BSE over scrapie and when used in sequential rounds of PMCA have demonstrated amplification specificity to BSE, even when BSE is present with a vast excess of different scrapie isolates [ 113 , 114 ]. The assay was shown to be far superior to ELISA and western blot tests for detecting ovine BSE in the presence of a large excess of scrapie agent [ 114 ].…”
Section: In Vitro Replication Of Prion Typesmentioning
confidence: 99%